Environmental effects of ozone depletion and its interactions with climate change: Progress report, 2016. Issue 2 (26th January 2017) - United Nations Environment Programme, Environmental Effects Assessment Panel,
Abstract : After entering Earth's atmosphere, solar UV radiation is selectively attenuated by a variety of gaseous, particulate, and dissolved compounds. These include ozone and smoke in the atmosphere, and dissolved organic carbon in both inland waters and marine ecosystems. Abstract : The Parties to the Montreal Protocol are informed by three Panels of experts. One of these is the Environmental Effects Assessment Panel (EEAP), which deals with two focal issues. The first focus is the effects of UV radiation on human health, animals, plants, biogeochemistry, air quality, and materials. The second focus is on interactions between UV radiation and global climate change and how these may affect humans and the environment. When considering the effects of climate change, it has become clear that processes resulting in changes in stratospheric ozone are more complex than previously believed. As a result of this, human health and environmental issues will be longer-lasting and more regionally variable. Like the other Panels, the EEAP produces a detailed report every four years; the most recent was published as a series of seven papers in 2015 ( Photochem. Photobiol. Sci., 2015, 14, 1–184). In the years in between, the EEAP produces less detailed and shorter Progress Reports of the relevant scientific findings. The most recent of these was for 2015 ( Photochem. Photobiol. Sci ., 2016, 15, 141–147). The present Progress Report for 2016 assesses some of the highlights and new insights with regard to the interactive nature of the direct and indirect effects of UV radiation, atmospheric processes, and climate change. The more detailed Quadrennial Assessment will be made available in 2018.